串联盘输送机钢丝绳牵引和链条牵引两种牵引形式运动学分析 - 石树林; 栾丽君; 李效志 (Jixie chuandong)
The Continuous Conveyor of series tyay transporter has two types of traction:the steel wire rope traction and chain traction.the velocity and the acceleration about the steel wire rope and chain are analysed,and the corresponding curve are drawn.The result indicates that variational scope the velocity and the acceleration change scope about the steel wire rope traction is smaller,and the movement is steadier.